Determining the style of conducting a fight of qualified boxers based on neurodynamic indicators using multivariate analysis methods - D.V. Safronov; V.Yu. Kozin; Zh.L. Kozina; A.V. Basenko; I.O. Riabenkov; S.B. Khrapov (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
Purpose: to justify the use of psychophysiological indicators to determine the style of conducting a fight in boxing. Material and methods. The study involved 27 qualified boxers of the middle weight category of 22-25 years. Athletes were tested on psychophysiological indicators. Initially, the determination of the psychophysiological capabilities of athletes was carried out. Then, using a cluster analysis of psychophysiological indicators, the athletes were divided into groups and the features of the styles of conducting a duel between the athletes of each group were analyzed using an expert assessment of their technical and tactical actions. Next, a distinction was made between the psychophysiological indicators of the athletes of the formed groups, i.e. different fighting styles. Results. Cluster analysis of indicators of psychophysiological testing showed the presence of 3 groups of athletes. An expert evaluation of the boxing match styles included in each group showed that the first group included boxers of the counterattack style, "Sluggers", the second group included athletes of the attacking style, "Swarmers (in-fighter, crowder)", the third group included athletes of the counterattack and defensive styles, "The out-boxers (out-fighter, boxers)". Boxers - "Sluggers" have higher mobility of nervous processes in comparison with representatives of other styles. Boxers - "pace" are distinguished by significantly higher neurodynamic endurance. "Attackers" - "Swarmer (in-fighter, crowder) " are distinguished by a higher strength of the nervous system, determined by the number of errors in the test for the speed of a complex reaction in the feedback mode. Conclusions. Psychophysiological and neurodynamic indicators are informative for determining the inclinations of boxers to a particular style of conducting a duel. This provision can be applied at all stages of training athletes to quickly and effectively determine propensities for a particular style of conducting a duel based on innate neurodynamic and psychophysiological characteristics.